Realisasi Keterbukaan Informasi Publik Pada Lingkup KementerianDalam Menunjang Pembaharuan Sistem Hukum Nasional (PSHN) - Natasya Klarisa Paruntu; Wilma Silalahi (JURNAL USM LAW REVIEW, 2025)
The objective of this study is to analyze the rights, obligations, roles, and level of compliance of ministries as public bodies in effectively implementing public information disclosure. The research is grounded in the importance of transparency and accountability as a manifestation of the fulfillment of human rights in governance, despite the fact that its implementation still faces various challenges across several ministries. The urgency of this study lies in the need for a comprehensive evaluation of compliance with public information disclosure standards to strengthen public trust and prevent the misuse of authority. This research employs a normative juridical approach with conceptual and legislative analysis, complemented by empirical data from the assessment results of the Indonesian Ombudsman. The findings reveal that public information disclosure within ministries remains suboptimal, as indicated by the limited availability of public information lists, service charters, and facilities for special-needs users. The novelty of this study lies in its analysis of public information disclosure from the perspective of the National Legal System Reform (PSHN), integrating both normative review and empirical evidence. The study concludes that strengthening regulations, enhancing the capacity of Public Information and Documentation Officers (PPID), and optimizing oversight are essential. Recommendations include policy harmonization and increasing ministerial commitment to making public information disclosure an integral part of national legal reform.   Tujuan penelitian ini adalah untuk menganalisis hak, kewajiban, peran, dan tingkat kepatuhan kementerian sebagai badan publik dalam mengimplementasikan keterbukaan informasi publik secara efektif. Latar belakang penelitian berangkat dari pentingnya transparansi dan akuntabilitas sebagai wujud pemenuhan Hak Asasi Manusia (HAM) dalam penyelenggaraan pemerintahan, meskipun praktiknya masih menghadapi berbagai kendala di sejumlah kementerian. Urgensi penelitian terletak pada perlunya evaluasi menyeluruh terhadap pemenuhan standar KIP guna memperkuat kepercayaan publik dan mencegah penyalahgunaan kewenangan. Metode penelitian menggunakan pendekatan yuridis normatif dengan analisis konseptual dan perundang-undangan, dilengkapi data empiris dari hasil penilaian Ombudsman Republik Indonesia. Hasil penelitian menunjukkan bahwa keterbukaan informasi publik di kementerian belum optimal, terlihat dari rendahnya ketersediaan daftar informasi publik, maklumat layanan, dan fasilitas bagi pengguna berkebutuhan khusus. Kebaruan penelitian ini terletak pada analisis KIP dari perspektif Pembaruan Sistem Hukum Nasional (PSHN) yang memadukan kajian normatif dan data empiris. Penelitian menyimpulkan bahwa penguatan regulasi, peningkatan kapasitas Pejabat Pengelola Informasi dan Dokumentasi (PPID), serta optimalisasi pengawasan sangat diperlukan. Rekomendasi penelitian meliputi harmonisasi kebijakan dan peningkatan komitmen kementerian untuk menjadikan KIP sebagai bagian integral dari pembaruan hukum nasional.